El tratado de libre comercio y su relación con el crecimiento económico de la macro región selva, durante el periodo 2007 - 2020 - Lopez Inuma, Lady Lhi (2022)
This study analyzes the relationship of free trade agreements in the economies of the departments of the Jungle Macroregion during the period 2007 to 2020, for which a quantitative methodology was acquired due to its nature, and correlational due to its level of explanation. A simple panel data regression model with fixed effects and structural break was also achieved. The research concludes that the series presents statistically significant parameters, being the most influential factor in economic growth the type of structural change in terms of the adoption of free trade agreements, exports, in this sense, it is necessary to increase our global openness and foreign trade to boost the economic growth of the departments of the jungle macro-region.